Mengembangkan Kerangka Lingkungan Kondusif untuk Menganalisis Dampak Infrastruktur Bisnis terhadap Pertumbuhan UMKM melalui Konektivitas Pasar di Kota Balikpapan - Abdulloh Abdulloh; Budi Eko Soetjipto; Ludi Wishnu Wardana (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study aims to examine the influence of market connectivity on the growth of micro, small, and medium enterprises (MSMEs) in Balikpapan City and to develop an Enabling Environment Framework that supports MSME growth. Using a quantitative approach with Structural Equation Modeling (SEM), data were collected through questionnaires distributed to MSMEs across various sectors. The results of the analysis indicate that market connectivity positively influences MSME innovation. However, its direct effect on MSME growth is insignificant, suggesting that innovation is a mediating variable in this relationship. The study concludes that while market connectivity does not directly promote growth, the innovation it stimulates is crucial for enhancing MSME performance. The recommendations include strengthening digital infrastructure, providing targeted training programs, and facilitating business networks to create a more conducive environment for MSME development. The proposed Enabling Environment Framework is expected to serve as a practical guide for stakeholders to enhance the contribution of MSMEs to the local economy.